Advances in single cell Raman spectroscopy technologies for biological and environmental applications. (August 2020) - Wang, Dongqi; He, Peisheng; Wang, Zijian; Li, Guangyu; Majed, Nehreen; Gu, April Z
Abstract : The increasing sophistication of single cell Raman spectroscopy (SCRS) via its integrations with other advanced analytical techniques and modern data analytics, enable unprecedented exploration of complex biological and environmental samples with significantly improved specificity, sensitivity, and resolution. Because of the merits of being high-resolution, label-free, non-invasive, molecular-specific, culture-independent, and suitable for in situ, in vitro or in vivo analysis, the SCRS-derived techniques offer abilities superior to conventional bulk measurements for environmental and biological studies. Here, we provide a comprehensive and critical review of the most recent advances in the development and application of SCRS-enabled technologies, with focus on those biomolecular and cellular high-resolution applications in environmental and biological fields. The basic principles, unique advantages, and suitable applications, as well as recognized limitations for each technology are recapitulated. The remaining challenges, research needs and future outlook are discussed. We predict that SCRS-enabled technologies are earning its place as a routine and powerful tool in many and rapidly expanding applications across disciplines.